PERAN JRO MANGKU SEBAGAI OPINION LEADER DALAM KOMUNIKASI KEBENCANAAN GUNUNG AGUNG DI AMERTABHUANA, KARANGASEM, BALI - Amelita Lusia Cecilia (Jurnal Sosial Humaniora Terapan, 2022)
Indonesia is the largest archipelago in the world, located between the continents of Asia and Australia, as well as the Indian and Pacific Oceans. It is located at the confluence of three of the world's active tectonic plates, namely the Indo-Australian, Eurasian, and Pacific plates, so it has the potential to be prone to natural disasters, including volcanic eruptions. The handling of these mountain disasters has tended to be less effective for various  reasons. One of the important efforts to do is through mitigation, which is a series of efforts to reduce disaster risk, both through physical development as well as awareness and capacity building in dealing with disaster threats. The forms of disaster mitigation activities includeeducation, counseling, and training both conventionally and modernly. In terms of conventional disaster mitigation, it can be done through opinion leaders, such as Balinese Hindu religious leaders in the Karangasem area. This research was conducted to see the role of Pemangku or Jero Mangku, namely people who are purified through the Ekajati/mawinten process, in conveying information about the eruption of Mount Agung. He serves the congregation in the temple. For Balinese Hindus, he is considered a human intermediary with the Creator, so his words are believed to beinstructions from the Almighty. This study uses a qualitative method with a literature study approach. The results showed that local people who havecultural values that are closely related to Balinese Hinduism, hear the information conveyed by Jro as something that contains the truth because Jro has a close relationship with Sang Hyang Widhi (the Creator). This shows that in mitigating the Mount Agung disaster, maximum efforts are needed to involve the role of Jro Mangku.Keywords: Mitigation, volcanoes, disasters, religious leaders, Balinese Hindus, opinion leader